Criteria Assessment of a Expect Teacher for Effective Teaching - H Dargahi; P Hamouzadeh; J Sadeghifar; M Raadabadi; M Roshani; M Salimi; P Soltanzadeh (Tehran University of Medical Sciences, 2011)
Background and Aim: Identifying criteria of expert teacher and efforts to strengthen and use them in teaching by teachers will enhance the learning process. In this way, one of the important methods is taking the views of students. This study was conducted to determine the characteristics of an expert teacher for effective teaching from the viewpoints of allied medical students at Tehran University of Medical Science. Materials and Methods: In this cross-sectional study, 200 BSc of allied medical students at were included employing simple random sampling method. Data collection was done employing a self administrated questionnaire. Validity and reliability of questionnaire was calculated. Data analysis was carried out by t-test and SPSS software. Results: Some criterias like dominance in the scientific subjects (86.8%), power of expression and transmission the training materials (86.2%), respect for students(85.6%), good mood(85%) and work with ethic and sense of responsibility (84.4%) are important criteria for expert teacher. Furthermore, no significant relationship was found between gender and field of study and the above-mentioned four domains (p> 0/05). Conclusion: Teaching ability was the most important factor for teaching process from he view of the students which could be paid attecntion in teachers' assessment program.